Perbedaan Kecukupan Asupan Gizi Berdasarkan Status Anemia Pada Siswi SMA Negeri 4 di Kecamatan Marpoyan Damai Kota Pekanbaru - Wahyuning Lestari; Feri Ilham; Adillah Rahmatul Ummi; Lukluk Ul Masykuroh; Fachriani Putri (Fakultas Kedokteran Universitas Riau, 2026)
According to the World Health Organization (WHO) in 2023, anemia is a global health problem widely experienced by women of reproductive age and remains a concern among adolescent girls. This study aimed to determine the prevalence of anemia and differences in macro- and micronutrient intake adequacy based on anemia status among female students at SMA Negeri 4 Marpoyan Damai District, Pekanbaru. A quantitative cross-sectional study was conducted in August 2024 involving 45 tenth-grade female students selected through simple random sampling. Dietary intake was assessed using 2x24-hour food recall and analyzed with NutriSurvey, while hemoglobin levels were measured using a hemoglobin meter. Bivariate analysis was performed using the Mann-Whitney test and independent t-test (p<0.05). The anemia prevalence was 13.3%. Most participants had inadequate macro- and micronutrient intake compared with the Recommended Dietary Allowance. No significant differences were found in carbohydrate (p=0.483), fat (p=0.071), protein (p=0.151), iron (p=0.483), folate (p=0.903), vitamin B12 (p=0.092), and vitamin C (p=0.664) intake between anemic and non-anemic students. In conclusion, anemia prevalence was relatively low; however, overall nutrient intake remained inadequate and showed no significant differences based on anemia status.